2022
DOI: 10.1177/13621688221125558
|View full text |Cite
|
Sign up to set email alerts
|

Understanding EFL teachers’ wellbeing: An activity theoretic perspective

Abstract: Teaching, as a physically, emotionally, and socially demanding profession, subjects teachers to multiple sources of stress and challenge, jeopardizing their wellbeing and adversely affecting their performance in turn. English language teaching is no exception to this unwelcome trend. The study of the factors affecting English as a foreign language (EFL) teachers’ perceived wellbeing in the workplace environment allows us insight into how teacher wellbeing can be enhanced and maintained in the face of challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In addition, Mairitsch et al (2021) investigated the well-being of 14 preservice language teachers. Drawing on interviews, the study findings indicated that factors such as management of time and the specific social language had an important role in the teachers' well-being, a finding also reported in Ebadijalal and Moradkhani (2022) in the context of Iran.…”
Section: Language Teacher Well-beingmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, Mairitsch et al (2021) investigated the well-being of 14 preservice language teachers. Drawing on interviews, the study findings indicated that factors such as management of time and the specific social language had an important role in the teachers' well-being, a finding also reported in Ebadijalal and Moradkhani (2022) in the context of Iran.…”
Section: Language Teacher Well-beingmentioning
confidence: 67%
“…Considering that research (e.g., Atai et al, 2022;Derakhshan et al, 2023;Kaivanpanah et al, 2021) has extensively shown the profound effect of contextual factors on EAP teachers' emotions, identities, and professional memberships, such factors could also influence EAP teachers' well-being as well. However, it is not clear how context shapes the teachers' wellbeing, especially in the Iranian context where factors shaping well-being could function more substantially (see Derakhshan et al, 2023;Ebadijalal & Moradkhani, 2022). In response to the lack and significance of research on EAP teacher well-being, the present study draws on the theoretical framework of activity theory and explores Iranian EAP teachers' well-being.…”
mentioning
confidence: 98%
“…Teacher Wellbeing Since the 1960s, the idea of wellbeing, in general, has gained momentum (McCallum et al, 2017), motivating a still-growing body of research focused on what it is, how to achieve it, and how to maintain it over time (Brown & Ralph, 1992;Dewaele et al, 2023;Ebadijalal & Moradkhani, 2022;McCallum & Price, 2010;Ryan & Deci, 2001;Van Petegem et al, 2005;Weinstein, 1988Weinstein, , 1989. The World Health Organization (1947) defined wellbeing as a "state of complete physical, mental and social wellbeing and not merely the absence of disease or infirmity" (p. 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although heavy workload and family health issues were found to erode language teachers' wellbeing in MacIntyre et al's (2020) study, the participants who used techniques based on approach rather than avoidance, manifested higher wellbeing levels. Meanwhile, navigating through the main factors deteriorating teacher wellbeing, numerous researchers (Ebadijalal & Moradkhani, 2022;Pourbahram & Sadeghi, 2022) have highlighted the devastating influence of unhealthy relationship patterns (between teachers and learners/ colleagues/staff) on teacher wellbeing. Specifically, conversion to online platforms heavily influenced the way people communicated; and consequently, the quality of relationships went downhill.…”
Section: Literature Reviewmentioning
confidence: 99%